2004
DOI: 10.1099/vir.0.80235-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel pestivirus associated with deaths in Pyrenean chamois (Rupicapra pyrenaica pyrenaica)

Abstract: During investigations into recent population decreases in Pyrenean chamois (Rupicapra pyrenaica pyrenaica) 21 animals found dead or dying were necropsied. Immunohistochemistry revealed the presence of a pestivirus in organs from two of the 21 chamois. From one of these animals a pestivirus was isolated from the spleen, skin and serum. The virus had better growth in ovine than in bovine cells and was neutralized most effectively by an anti-border disease virus (BDV) reference antiserum. Using panpestivirus and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
69
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 25 publications
8
69
0
Order By: Relevance
“…Antibodies against viral pathogens include bovine herpesvirus 1, encephalomyocarditis virus (Gentile et al 2000), bovine parainfluenza type 3 virus, bovine respiratory syncytial virus (Gaffuri et al 2006), and pestivirus (Gentile et al 2000;Arnal et al 2004;Hurtado et al 2004;Gaffuri et al 2006;Marco et al 2007;Pioz et al 2007;Marco et al 2008). Regarding bacterial agents, antibodies have been detected against Brucella melitensis (Garin-Bastuji et al 1990), Mycoplasma conjunctivae (Giacometti et al 2002;Gaffuri et al 2006), Salmonella enterica, Coxiella burnetii (Pioz et al 2008), Leptospira interrogans (Gentile et al 2000), and Chlamydophila abortus (Pioz et al 2008;Salinas et al 2009).…”
Section: Introductionmentioning
confidence: 95%
“…Antibodies against viral pathogens include bovine herpesvirus 1, encephalomyocarditis virus (Gentile et al 2000), bovine parainfluenza type 3 virus, bovine respiratory syncytial virus (Gaffuri et al 2006), and pestivirus (Gentile et al 2000;Arnal et al 2004;Hurtado et al 2004;Gaffuri et al 2006;Marco et al 2007;Pioz et al 2007;Marco et al 2008). Regarding bacterial agents, antibodies have been detected against Brucella melitensis (Garin-Bastuji et al 1990), Mycoplasma conjunctivae (Giacometti et al 2002;Gaffuri et al 2006), Salmonella enterica, Coxiella burnetii (Pioz et al 2008), Leptospira interrogans (Gentile et al 2000), and Chlamydophila abortus (Pioz et al 2008;Salinas et al 2009).…”
Section: Introductionmentioning
confidence: 95%
“…For example, 16% of seropositive chamois were found in the Central Pyrenees, and 25.5% of the investigated chamois were positive in an Italian study. 2,19 There, the investigators stated that presence of BDV among extensively kept domestic sheep may be the cause for the high pestivirus antibody prevalence in that chamois population. A recent Swiss study in sheep in Grisons showed a seroprevalence of 32.4% and 33.7% for BVDV-1 and BDV-1, respectively.…”
mentioning
confidence: 99%
“…Moderate hyperplasia with orthokeratotic hyperkeratosis was also observed in skin . The strains isolated during these outbreaks were BDV-4 (Arnal et al, 2004;Frö lich et al, 2005). A retrospective study of archived sera and spleen showed that the populations studied had been infected by BDV-4 strains at least as early as 1990.…”
Section: Introductionmentioning
confidence: 99%